Anāshir An-Nadzariyyah As-Sulukiyyah fī Ta’līm al-Mufradāt (Dirāsah Tahlīliyyah Washfiyyah) - Agung Nurcholis; Qudwatun Hasanah (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2020)
Vocabulary plays an important role in understanding a person’s thoughts and experiences, spoken or written. This is evidence that a person’s understanding of vocabulary plays an important role in the process of spoken or written language in academic or everyday life—especially for the language learner. Scholars believe that the Arabic language is the richest language in that it consists of various vocabularies, most of them related to cultural concepts. Vocabulary is a tool for carrying meaning, and at the same time it is a tool to think, because the speaker can think and translate what has crossed into his mind and thought with the words he wants. Behavioral theory is one of the theories in the science of psychology that investigates human behaviors and types of stimulus responses presented to them, not related to feelings or the construction of other creation. This theory has been established since the nineteenth century. The classical strand theory was a result of the experiments of Ivan Pavlov, the founder of the behavioral theory’s future development. This theory examined human behavior, which is an apparent movement of some stimuli. It is best known for Reinforcement Response Theory Stimulus. One of the characteristics of behavioral theory is that the teacher is more active and effective, although the learner does not realize what he did, and the teacher becomes the exciter of the inputs and processes of human behavior. The research aims to delve into behavioral theory and to understand it. It also aims to know how to implement this theory in teaching vocabulary, in order to teach foreign languages in general and the Arabic language in particular. Behavioral theory is one of the theories used in teaching vocabulary. It is hoped that this research will solve the problems faced by learners in the future.